Қарақалпақ халық эпосларында мифлик сюжетлик мотивлер (SCIENCE and SOCIETY, 2019)
The articale is devoted to the issues of inter connection and reasons of mythological motives in the poetic composition of the Kara- kalpak folk eposes. The author gives the comparative analysis in typological and artistic aspects of mythological motives in the plot of an epos.